2007
DOI: 10.1002/crat.200610807
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of SrMnO3 powders with different morphologies by hydrothermal method

Abstract: By using two different reagents as the starting materials, SrMnO 3 crystallines with two different morphologies rhombus-like and rod-like, have been directly synthesized by hydrothermal conditions. The effects of the hydrothermal parameters on the quality of the SrMnO 3 samples were given for the fist time. And a preparative mechanism for the formation of different morphologies using different reagents during the hydrothermal reaction has been discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
(32 reference statements)
0
11
0
Order By: Relevance
“…The alkali earth manganates SrMn IV O 3 and BaMn IV O 3 can also be prepared in one step under mild hydrothermal conditions (T o 240 1C). [158][159][160][161] These are again examples of 'hexagonal perovskites', but in this case they have structures constructed from chains of face-shared {MnO 6 } octahedra, Fig. 12b, so are not strictly perovskite materials.…”
Section: Manganitesmentioning
confidence: 99%
“…The alkali earth manganates SrMn IV O 3 and BaMn IV O 3 can also be prepared in one step under mild hydrothermal conditions (T o 240 1C). [158][159][160][161] These are again examples of 'hexagonal perovskites', but in this case they have structures constructed from chains of face-shared {MnO 6 } octahedra, Fig. 12b, so are not strictly perovskite materials.…”
Section: Manganitesmentioning
confidence: 99%
“…Spooren and Walton reported the first successful hydrothermal synthesis of 4H-SrMnO 3 but the resulting morphology was rather heterogeneous ranging from elongated prismatic microcrystals to microparticles. More recently, Zhu et al have shown the influence of the starting materials in the morphology of the SrMnO 3 particles obtained from hydrothermal conditions, forming rhombus-like shaped crystals when KMnO 4 , Mn(CH 3 COO) 2 and Sr(CH 3 COO) 2 were used as starting materials, and rod-like particles when synthesized from KMnO 4 , MnSO 4 and SrSO 4 , but no SrMnO 3 nanoparticles were attained. Moreover, Rizzuti et al obtained blade-shaped particles of 4H-SrMnO 3 by microwave assisted hydrothermal synthesis although still in the microscale.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical and experiment studies have been devoted to studying strontium manganites and cobaltite with the formulas SrMnO 3 and SrCoO 3 during the last several years [1,2]. The SrMnO 3 is known as a G-type antiferromagnetic insulator.…”
Section: Introductionmentioning
confidence: 99%